Detection of JAK2V617F Mutation in Chronic Myeloproliferative Disorders - Cruz AlemÃ¡n, Santos; Larios Roque, Adriana; Caldera Suazo, Uxmal; Santamaria Quesada, Carlos; Puller, Ann-Christin; Pernudy Ubau, Allan (Revista Cubana de Hematología, Inmunología y Hemoterapia, 2017)
Introduction: Myeloproliferative neoplasms (MPNs) comprise several hematological neoplasms such as polycythemia vera (PV), essential thrombocythemia (ET), and idiopathic myelofibrosis (IMF). Molecular lesions have been investigated as the underlying mechanism for the genesis of MPNs with the specific mutation in the Janus kinase 2 (JAK2) gene, JAK2 V617F, being most frequent. The variant JAK2 V617F protein is characterized by a substitution of valine for phenylalanine at position 617 (V617F) resulting in constitutively unregulated enzymatic activity. Objectives: Currently, the diagnoses of MPNs in Nicaragua are based solely on clinical presentation of the patient and routine blood analyses. We aim for the implementation of the molecular diagnosis of JAK2 V617F in order to allow for a more specific classification and to provide targeted therapy for positive patients. Methods: To detect the JAK2 V617F mutation in MPNs patients, a cross-sectional study was performed with 29 patients with clinical diagnosis of PV, ET, or IMF. DNA was extracted from whole peripheral blood using a commercial kit. A polymerase chain reaction (PCR) technique was carried out to detect the mutation at the genomic level using allele-specific primers. Results: This study represents the first report of JAK2 V617F analysis in Nicaragua. The mutation was detected in 14 out of 29 MPNS patients. Following the recommendations of the World Health Organization (2016), we suggest the molecular testing for the JAK2 V617F mutation as part of the initial diagnostic portfolio for patients suffering myeloproliferative neoplasms in Nicaragua and in the rest of Latin American countries.